Myoring implantation with and without cross-linking: Comparative study of pre and postoperative visual outcomes and pentacam indices - Morkos, Fathy Fawzy; Fawzy, Nader Fathy; El Bahrawy, Mohamed; Talaat, Omnia; Elkitkat, Rania Serag (European journal of ophthalmology, 2025)
ObjectivesComparing the visual, topographic, and aberrometric changes following Myoring implantation alone or combined with corneal cross-linking (CXL).MethodsThis retrospective, comparative study was conducted on keratoconus (KC) patients with moderate, central KC who sought medical advice at Watany Eye Hospital, Cairo, Egypt. Group 1 patients performed femtolaser-assisted Myoring implantation, while group 2 patients performed Myoring implantation with CXL.ResultsGroup 1 included 44 eyes, and group 2 comprised 40 eyes. The mean follow-up interval was 2.34 years ± 2.25. There was a significant postoperative improvement in subjective refraction for both groups. Patients of group 1 showed statistically significant reductions in postoperative topographic astigmatism, K readings, Index of Surface Variance, horizontal coma, and spherical aberrations. In contrast, patients of group 2 only showed statistically significant improvements in K readings and horizontal coma. Patients of group 1 developed higher improvements in topographic astigmatism and K max compared to group 2.ConclusionAlthough the combined technique was non-inferior to implanting the Myoring alone regarding visual, refractive, and keratometric improvements, Myoring implantation alone showed better results, mainly in topographic astigmatism. Hence, our study leans in favor of Myoring implantation without the need for additional CXL